3D Printing Experimental Validation of the Finite Element Analysis of the Maxillofacial Model - Shu, Jingheng; Luo, Haotian; Zhang, Yuanli; Liu, Zhan (Frontiers in Bioengineering and Biotechnology, 2021)
Contacts used in finite element models were considered as the best simulation for interactions in the temporomandibular joint (TMJ). However, the precision of simulations should be validated through experiments. 3D printing models with the high geometry and loading similarities of the individuals were used in the validation. The study aimed to validate the finite element models of the TMJ using 3D printing models. 5 asymptomatic subjects were recruited in this study. 3D models of mandible, disc, and maxilla were reconstructed according to cone-beam computed tomography (CBCT) image data. Polylactic acid was chosen for 3D printing models from bottom to top. 5 pressure forces corresponding to the central occlusion were applied to the 3D printing models. Ten strain rosettes were distributed on the mandible to record the horizontal and vertical strains. Contact was used in the finite element models with the same geometry, material properties, loadings, and boundary conditions as 3D printing models to simulate the interaction of the disc-condyle, disc-temporal bone, and upper-lower dentition. The differences of the simulated and experimental results for each sample were less than 5% (maximum 4.92%) under all the 5 loadings. In conclusion, it was accurate to use contact to simulate the interactions in TMJs and upper-lower dentition.